An Appraisal Among Wired, Hybrid and Wireless Smart Homes to Mitigate Electromagnetic Radiation - Raveendran, Reshna; Tabet Aoul, Kheira Anissa (Frontiers in Built Environment, 2022)
The global Covid-19 pandemic caused a rapid transitioning to remote work settings, one likely to subside post-pandemic, resulting on people spending more time at home for work or study. The global pandemic defined a new normal and recovery is expected to be digital and heavily relying on technology. Smart buildings which are envisioned to be the next paradigm shift in the built environment are also foreseen as a response solution to aid in situations like pandemic. However, such a move yields benefits as well as risks, prompting wide debates on the priority to safeguard building occupants health, safety and well-being. Researchers, designers and engineers are seeking solutions to incorporate or modify design features in the indoor environment that prioritize the dwellers' health and wellness. Though benefits of smart and IoT devices aid in monitoring health and aiding the elderly, radiation from these wireless devices may cause harm to human health, especially those with weaker health, as indicated by several research findings. Some of the negative impacts from wireless radiation include cell damage, cancer, tumor, change in hormonal levels, and neurological damage. Thus, this study seeks to determine the difference in radiation level inside a wired, hybrid and a wireless smart home through Computer Simulation Technology (CST) simulation. The results revealed that wireless produced 26.55% more radiation than wired scenario at 2.45 GHz. Further, the total EMR and radiation patterns are dependent on several factors like proximity of IoT and smart devices to building walls and interior furnishings, frequency of operation and not just a linear relationship to the number of wireless devices added in the solution domain. This study recommends the incorporation of wired and hybrid design instead of wireless to create a safer dwelling indoor environment.